ECONOMIC REFORMS AND ENTRY BARRIERS IN INDIAN MANUFACTURING - Suresh Babu M (Centre for Development Studies-WP331, 2002)
Institutional regulations by way of licensing and capacity restrictions have often been considered as barriers to competition in Indian industry. As most of these regulations have given way for market signals an increase in the number of entrants and alterations in the conditions of entry, mainly the barriers to entry are expected. In this paper I attempt to analyse the extent of barriers to entry in Indian manufacturing by empirically quantifying the height of these barriers. Econometric estimation of the height of the barriers for 1991 and 1996 shows that the height of barriers increased in 1996 at the aggregate level. An examination at the disaggregate level reveals that in almost all the industries examined from a sample of firms drawn from the CMIE the height of the barriers have increased in 1996 compared to 1991. The dilution and dismantling of commands and controls intended to ease entry have thus paved the way for the erection and strengthening of market barriers which have grown over time.